PERBANDINGAN PREFERENSI PESERTA BPJS TERHADAP KUALITAS PELAYANAN DI RUMAH SAKIT DR. PIRNGADI DAN RUMAH SAKIT MARTHA FRISKA MEDAN TAHUN 2015 - wilda try wahyuni; Abdul Jalil Armi Arma; Maya Fitria (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT Dissatisfaction of BPJS members toward hospital service quality encourages them to have health service based on their preferences, so their need and hope is properly fulfilled. The objectives of this research are to identify and compare the preferences of BPJS members toward service quality in General Hospital of Dr. Pirngadi and Martha Friska Medan by using conjoint analysis. There are 5 attributes of hospital services, i.e. reliability, responsiveness, assurance, empathy and tangible in which each attribute consists of sub Attribute and Level. The conjoint analysis is one of the methods for obtaining the level combination and most important attribute based on patients’ preferences in which each hospital serves 50 BPJS patients and the sample was taken by purposive sampling method. The result of this research indicates that the preferences of BPJS members toward service quality based on the sequences of the most important sub attributes  between the General Hospital of Dr. Pirngadi and Martha Friska were responsiveness, assurance and empathy, while the differences were found on reliability and tangible.  The level combination of the same sub attributes  between those general hospitals were found on empathy attribute, and for the attribute of reliability, responsiveness, assurance, tangible, it produced the different combination. It is suggested to the General Hospital of Dr. Pirngadi and Martha Friska to provide the health service based on the preferences of BPJS members and for the future study, it is suggested to apply the conjoint analysis in another health case.